The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1997
DOI: 10.3354/meps151017
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of tidal resuspension of microbiota:testing the effects of sediment cohesiveness and bioturbation using flume experiments

Abstract: Resuspension of the top few sediment layers of tidal mud flats is known to enhance planktonic biomass of microbiota (benthic dlatoms and bacteria). This process is mainly controlled by tidal shear stress and cohesiveness of mud, and 1s also influcnced by bioturbation activities. Laboratory experiments in a race track flume were performed to test the interactive effects of these factors on both the critical entrainment and resuspension kinetlcs of microbiota from sllt-clay sediments from the hlarennes-01eron Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
40
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(42 citation statements)
references
References 17 publications
2
40
0
Order By: Relevance
“…Different macrofaunal assemblages are known to affect sediment stability in different ways (Meadows et al, 1990;Blanchard et al, 1997;Meadows et al, 1998;Widdows et al, 1998bWiddows et al, , 2000Willows et al, 1998;Austin et al, 1999;Riethmüller et al, 2000;Andersen, 2001;de Deckere et al, 2001). For example, on Eden Grid A, N. diversicolor had a net positive association with sediment stability, possibly due to the secretions produced during burrow formation and increased drainage of the sediment.…”
Section: Discussionmentioning
confidence: 99%
“…Different macrofaunal assemblages are known to affect sediment stability in different ways (Meadows et al, 1990;Blanchard et al, 1997;Meadows et al, 1998;Widdows et al, 1998bWiddows et al, , 2000Willows et al, 1998;Austin et al, 1999;Riethmüller et al, 2000;Andersen, 2001;de Deckere et al, 2001). For example, on Eden Grid A, N. diversicolor had a net positive association with sediment stability, possibly due to the secretions produced during burrow formation and increased drainage of the sediment.…”
Section: Discussionmentioning
confidence: 99%
“…The common mud snail Hydrobia ulvae is a widespread deposit feeder at fine-grained sediments on European intertidal flats and an evaluation of the effect of this species on the erodibility of the bed is therefore of major importance. The snail may occur in densities of up to about 300 000 individuals m À 2 (Blanchard et al, 1997;Austen et al, 1999;Jensen, 1992;Lillebø et al, 1999). Some studies (Blanchard et al, 1997;Andersen, 2001a) have indicated that H. ulvae increase the erodibility of their substrata.…”
Section: Introductionmentioning
confidence: 99%
“…The snail may occur in densities of up to about 300 000 individuals m À 2 (Blanchard et al, 1997;Austen et al, 1999;Jensen, 1992;Lillebø et al, 1999). Some studies (Blanchard et al, 1997;Andersen, 2001a) have indicated that H. ulvae increase the erodibility of their substrata. Not only do the snailshells themselves increase the roughness of the bed, but so does the surface tracking caused by the feeding activity of the snails (Blanchard et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, small benthic faunal (e.g. the gastropod Hydrobia ulvae) may disturb the sediment surface by creating tracks and forming faecal aggregates that, together with the animal itself, increases the overall bed roughness, making the surface more susceptible to hydrodynamic erosive forces (Blanchard et al, 1997;. Also sediment reworking by larger burrowing and deposit-feeding macrofauna (e.g.…”
Section: Introductionmentioning
confidence: 99%